Flow patterns and noise of a choked gas jet expanding into a duct - Krystyna J. WITCZAK (Archives of Acoustics)
Axi-symmetric, choked air outflow into a duct with an abrupt enlargement of its cross-section was investigated in order to establish the relations between the flow pattern and the aerodynamic noise generated. Four main kinds of flow structure, possessing different acoustic properties, were found in the cases studied of the outflow from convergent circular and annular nozzles. These patterns correspond to the occurrence of: cellular structure, self-excited oscillations, single shock wave (noise minimum) and supersonic flow. An acoustic feedback type source of sound can appear under certain circumstances in the cellular structure. The self-excited shock wave and pressure oscillations produce noise characterized by discrete frequencies in the sound pressure level spectrum. The reasons for the minimum noise generation, which takes place before the reattachment of the supersonic stream boundary to the duct wall, are explained. Prevention of strong oscillations by the insertion of spoilers at the nozzle lip reduces the noise significantly over a wide range of supply pressures, however it increases the noise minimum due to turbulence intensity growth. Recommendations for nozzle and duct geometry for noise reduction are given.